Two new species of the macropsine leafhoppers (Hemiptera: Cicadellidae: Eurymelinae) from Japan, with description of a new subgenus - Okudera, Shigeru; Hayashi, Masami (Zootaxa, 2024)
Two new macropsine species, Celopsis yaeyamana sp. nov. and Pediopsoides (Glaphyropsis) aurantescens subgen. & sp. nov. are described and illustrated from the Ryukyu Islands of Japan. Four Celopsis species, C. membrana (Zhang), C. montaninversa (Yang & Zhang), C. trifurcata (Li, Dai & Li) and C. rhombica (Li, Dai & Li) are transferred to the new subgenus Glaphyropsis.